CONTEXT MATTERS: EXPLORING THE DYNAMICS OF IFRS ADOPTION IN INDIA AND PAKISTAN - Islam, Maruful; Hossain, Shayeed; Taki, Mohammad Khabbab (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2024)
The International Financial Reporting Standards (IFRS) are a universally accepted accounting practice framework. Established by the International Accounting Standards Board (IASB), IFRS promotes transparency and comparability in financial reporting. This study focuses on adopting IFRS in India and Pakistan, intending to identify the factors influencing this adoption and examining the unique determinants specific to each country. A comparative analysis of IFRS adoption in India and Pakistan was conducted using historical analysis and secondary sources, including academic literature, books, research papers, publications from international financial institutions, and relevant websites. The study reveals that, while common factors influence IFRS adoption in both countries, contextual disparities significantly affect the decision-making process. Economic, social, legal, and political dimensions, intertwined with institutional factors, play a critical role in shaping the adoption or rejection of IFRS. This underscores that local context outweighs mere commonalities in determining IFRS adoption decisions, challenging oversimplified categorizations based solely on similarities. This research contributes to understanding the complexities of IFRS adoption in diverse socio-economic contexts, particularly in emerging economies such as India and Pakistan. By elucidating the interplay of various contextual factors, the study provides valuable insights for policymakers, standard-setting bodies, and practitioners navigating international accounting standards. Recognizing the multifaceted nature of influences on adoption decisions can inform more nuanced policymaking and facilitate smoother transitions towards global accounting standards, enhancing the quality and comparability of financial reporting worldwide.